Teaching characteristics based on the Integrated STEM approach in the scientific departments at the College of Science and Humanities at Prince Sattam bin Abdulaziz University: Views from the faculty members - Alasmari, Ibrahim Mohammed (Research Journal in Advanced Humanities, 2026)
The purpose of this study was to examine the extent to which teaching traits are available according to the integrated STEM approach in the scientific departments of the College of Science and Humanities at Prince Sattam bin Abdulaziz University, from the perspective of faculty members. The researcher employed a descriptive-analytical methodology. A questionnaire was developed based on the global framework for STEM education prepared by the New York Academy of Sciences. The questionnaire consisted of 86 indicators, distributed across three dimensions: basic competencies, (which included core skills and supporting traits), instructional design, and implementation. The study sample comprised 77 faculty members (39 males & 38 females). The results revealed that the extent to which teaching characteristics based on the integrated STEM approach are available, from the perspective of faculty members, was moderate across all dimensions and in the total score. Significant differences were found between male and female faculty members in favor of males regarding the availability of teaching attributes according to the integrated STEM approach. However, no significant differences were observed in the availability of these traits according to academic specialization across all dimensions or their total score. The study recommends enhancing professional development programs for faculty members in the scientific departments in line with STEM requirements, including training in essential skills such as critical thinking, problem-solving, creative thinking, and the use of digital technologies and computer sciences. It also emphasizes providing specialized training programs on designing integrated STEM units, including inquiry-based teaching, project-based learning, and linking concepts from science, engineering, and mathematics to real-world applications relevant to the local context.